Signaling in First-Price Auctions - Thomas Rieck (University of Bonn, Bonn Graduate School of Economics (BGSE), 2010)
It is commonly assumed in private value auctions that bidders have no information about the realization of the other bidders' valuations. Nevertheless, an informative public signal about the realization may be released by a bidder while he learns his own valuation. Using a simple discrete asymmetric first-price auction setting, we show that a bidder may indeed benefit from the presence of an informative signal about his own valuation. We characterize the optimal signal and show that a signal is not beneficial if it is too precise. The latter result carries over to a general continuous asymmetric first-price auction model. Finally, we use a specific signaling structure with uniform distributions to show that signaling need not be beneficial for any precision of the signal.
Keywords: D44; D82; 330; Asymmetric auction; first-price auction; signaling; Auktion; Asymmetrische Information; Signalling; Auktionstheorie